2, 4-Thiazolidinedione Treatment Improves the Innate Immune Response in Dairy Goats with Induced Subclinical Mastitis. (27th June 2017) - Rosa, Fernanda; Osorio, Johan S.; Trevisi, Erminio; Yanqui-Rivera, Francisco; Estill, Charles T.; Bionaz, Massimo
Abstract : Mastitis is a major disease in dairy cows resulting in significant economic losses. In vitro works suggest that ruminants peroxisome proliferator-activated receptor gamma (PPAR γ ) can aid in improving the response to mastitis and can control milk fat synthesis. The objectives of the present experiment were to test if treatment with the putative PPAR γ agonist 2, 4-thiazolidinedione (TZD) improves (1) the response to subclinical mastitis and (2) milk fat production. Lactating goats received daily injections of 8 mg/kg BW of TZD or saline for 3 weeks. After one week of TZD injection, half of the goats in each group received intramammary infusion of Strep. uberis or saline in both halves for a total of 4 groups (n = 6 /group). TZD treatment did not affect milk fat but had positive effect on milk somatic cells count, blood nonesterified fatty acids, inflammatory markers, and liver function. TZD significantly increased myeloperoxidase but did not affect leukocytes phagocytosis or insulin. TZD increased adipocytes size and had minor effect on expression of PPAR γ target genes in mammary epithelial cells but not in adipose tissue. Overall, TZD ameliorated the response to intramammary infection but the effect on milk fat synthesis and expression of related transcripts was less than expected.